Seasonal dynamics in abundance and species composition of nekton in the upper epipelagic layer of the western Bering Sea - Aleksey A. Somov (Известия ТИНРО)
The western Bering Sea is the feeding area for many nekton species with seasonally variable composition. Seasonal changes in abundance, composition and structure of the nekton community in the upper epipelagic layer (0-50 m) of this area are considered on the data collected in trawl surveys conducted by Pacific Fish. Res. Center (TINRO) in June-October of the 2003-2015, separately for the deep-water Aleutian and Commander Basins and shelf waters at Cape Navarin. The highest total abundance of nekton was observed in the middle August (2700 kg/km2, on average) and decreased significantly earlier (100 kg/km2 in early June) and later (200 kg/km2 in late October). The dominant species were pacific salmons (Oncorhynchus spp., in particular O. keta ), boreopacific gonate squid ( Boreoteuthis borealis ) and shortarm gonate squid ( Gonatus kamtschaticus ). Besides, walleye pollock ( Theragra chalcogramma ), pacific herring ( Clupea pallasii ) and capelin ( Mallotus villosus ) were abundant in the shelf waters. Three seasons are defined by the species structure: i) early summer from early June to middle July with dominance of pre-anadromous pink salmon O. gorbuscha and chum salmon ( O. keta ) and moderate species diversity (polydominance index 3.5-4.0); ii) summer from late July to middle September with absolute dominance of chum salmon (> 70 % of total nekton abundance) and low species diversity (1.5-2.0); and iii) autumn from late September to the end of October with dominance of chum salmon, sockeye salmon and boreopacific gonate squid in relatively equal proportion, mass appearance of pink salmon juveniles and high species diversity (4.5). Spatial patterns of the nekton distribution change between the seasons, too. They are formed in early summer by mass migrations of many species to the western Bering Sea from the east and south, reflect low intensity of the migrations in summer, and are determined by backward migrations toward the southeastern Commander Basin and further to the central Bering Sea and North Pacific in autumn.